2017
DOI: 10.1177/2325967117737020
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes After the Surgical Management of Isolated Anterolateral Leg Chronic Exertional Compartment Syndrome

Abstract: Background:Failure rates of up to 20% have been reported after fasciotomy for chronic exertional compartment syndrome (CECS). There is some evidence that postoperative failure and complication rates are higher in the posterior compartments of the lower leg than the anterolateral compartments. Isolated compartment surgery may put patients at risk of requiring revision surgery because of the risk of developing posterior compartment disease.Hypothesis:Isolated anterolateral fasciotomy for CECS, in the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…Although the MLLF technique appears to be effective in reducing pain, most patients reported some degree of leg pain at longer-term follow-up, in keeping with existing studies [6,13,14]. Abnormal sensation complicates up to 62% of fasciotomy procedures [6,8,10,[13][14][15][16][17][18][19][20][21]23], and the reasons for the slightly higher prevalence of sensory abnormalities we observed (67%) are unclear. Notably, only one-quarter of patients described constant sensory symptoms, with forty per cent reporting these only on activity.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although the MLLF technique appears to be effective in reducing pain, most patients reported some degree of leg pain at longer-term follow-up, in keeping with existing studies [6,13,14]. Abnormal sensation complicates up to 62% of fasciotomy procedures [6,8,10,[13][14][15][16][17][18][19][20][21]23], and the reasons for the slightly higher prevalence of sensory abnormalities we observed (67%) are unclear. Notably, only one-quarter of patients described constant sensory symptoms, with forty per cent reporting these only on activity.…”
Section: Discussionsupporting
confidence: 74%
“…Although non-operative management may be effective in some instances [4], CECS symptoms often persist [5] and lower limb fasciotomy an accepted surgical treatment to facilitate return to activity [6]. Fasciotomy may be performed open [6][7][8][9][10][11][12][13][14][15][16][17][18][19] or using a percutaneous or mini-open approach [20][21][22][23]. There is considerable variation in operative technique and reported outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Of those who returned, approximately 40% were at their presurgical level, while the remaining 60% were at a lower level of sport. 34 Gatenby et al 8 similarly investigated outcomes after isolated anterolateral compartment release and reported that 90% of patients return to sports at the same or higher level postoperatively. This study similarly notes that patients who required revision surgery were often returning to the operating room to release compartments previously not released.…”
Section: Discussionmentioning
confidence: 99%
“…12 Patients with high muscle pressure in the anterior or lateral compartment occasionally experience awkward foot sensations in the dermatome of the deep peroneal nerve (web space between first and second toes) or the superficial peroneal nerve (dorsum of foot), respectively. 5 Our patients were asked to indicate areas of altered skin sensation of the foot, if present, on a drawing. Approximately one-third of our patients reported alterations in skin sensation, possibly reflecting compression of either the deep or superficial peroneal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…It is our experience that some patients with ELP spontaneously report altered foot skin sensation, possibly reflecting compromised leg peripheral nerves in the presence of CECS. 5 A recent study indicated that patient pain drawings may offer a potential instrument contributing to identifying the cause of ELP. 12 Therefore, when patients experienced altered foot skin sensation and/or tingling, they were asked to mark this area on a drawing (Figure 1).…”
Section: Methodsmentioning
confidence: 99%